Othello - Shakespeare, William 1564-1616.; Zarate, Oscar, 1942- (New York : Ravette Books Limited, 1983)
Shakespeare's tragedy of jealousy and suspicion presented scene by scene in comic book format.
Keywords: Othello (Fictitious character) -- Drama; Interracial marriage -- Drama; Jealousy -- Drama; Muslims -- Drama; Plays; Cartoons and comics; Venice (Italy) -- Drama; Tragedies